2003
DOI: 10.1103/physrevb.68.045207
|View full text |Cite
|
Sign up to set email alerts
|

Internally consistent approach for modeling solid-state aggregation. II. Mean-field representation of atomistic processes

Abstract: A detailed continuum (mean-field) model is presented that captures quantitatively the evolution of a vacancy cluster size distribution in crystalline silicon simulated directly by large-scale parallel molecular dynamics. The continuum model is parameterized entirely using the results of atomistic simulations based on the same empirical potential used to perform the atomistic aggregation simulation, leading to an internally consistent comparison across the two scales. It is found that an excellent representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
3
30
0
1
Order By: Relevance
“…This conclusion can be contrasted starkly with the more common case of energetic stabilization of "magic" cluster sizes, such as for vacancy clusters. 49,50 In the energetic stabilization case, clusters of particular sizes are favored relative to others at low temperature because certain configurations minimize the formation energy ͑e.g., by the minimization of dangling bonds͒. However, at elevated temperature, this effect is obscured by entropic contributions and the formation free energy per vacancy is found to decrease almost monotonically with cluster size.…”
Section: A Probability Distribution Functions For Small Clusters At mentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion can be contrasted starkly with the more common case of energetic stabilization of "magic" cluster sizes, such as for vacancy clusters. 49,50 In the energetic stabilization case, clusters of particular sizes are favored relative to others at low temperature because certain configurations minimize the formation energy ͑e.g., by the minimization of dangling bonds͒. However, at elevated temperature, this effect is obscured by entropic contributions and the formation free energy per vacancy is found to decrease almost monotonically with cluster size.…”
Section: A Probability Distribution Functions For Small Clusters At mentioning
confidence: 99%
“…[38][39][40][41][42] Configurational entropy arises from the presence of numerous mechanically stable configurations that a defect cluster can assume within the lattice. Each of these configurations, ␣, ͑so called inherent structures͒ can be identified by a local energy minimum, V ␣ , in the multidimensional potential-energy landscape ͑PEL͒ that defines the overall system.…”
Section: Computational Framework For Single Cluster Thermodynamicmentioning
confidence: 99%
“…In fact, MD simulations with various potentials 17,18 indicate that the interaction extends up to the 4NN distance along the ͑110͒ direction, and somewhat less along other directions. Assuming that the vacancy-vacancy interaction is approximately isotropic, the interaction distance therefore can extend up to the 8NN interaction shell!…”
Section: B Kmc Bonding Modelmentioning
confidence: 99%
“…Assuming that the vacancy-vacancy interaction is approximately isotropic, the interaction distance therefore can extend up to the 8NN interaction shell! In our previous work, 11 it was further shown that this interaction distance was essentially independent of the local environment, and can be assumed to be constant.…”
Section: B Kmc Bonding Modelmentioning
confidence: 99%
See 1 more Smart Citation